2010
DOI: 10.1111/j.1748-7692.2009.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotope biogeochemistry to study marine mammal ecology

Abstract: Stable isotope analysis (SIA) has emerged as a common tool in ecology and has proven especially useful in the study of animal diet, habitat use, movement, and physiology. SIA has been vigorously applied to the study of marine mammals, because most species live in habitats or undergo large migrations/movements that make them difficult to observe. Our review supplies a complete list of published SIA contributions to marine mammal science and highlights informative case examples in four general research areas: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
767
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 469 publications
(817 citation statements)
references
References 235 publications
19
767
1
8
Order By: Relevance
“…Other methods of diet analysis (e.g., stable isotopes and fatty acids) result in qualitative information regarding trophic level and general categories of prey. Quantitative information from these indirect approaches require complete prey libraries (often diffi cult to obtain) in order to interpret diet to the species level (Budge et al, 2006;Newsome et al, 2010).…”
Section: Data Limitationsmentioning
confidence: 99%
“…Other methods of diet analysis (e.g., stable isotopes and fatty acids) result in qualitative information regarding trophic level and general categories of prey. Quantitative information from these indirect approaches require complete prey libraries (often diffi cult to obtain) in order to interpret diet to the species level (Budge et al, 2006;Newsome et al, 2010).…”
Section: Data Limitationsmentioning
confidence: 99%
“…Additionally, some items in the stomach are not recognizable, due to advanced decomposition, and there is no guarantee that identifiable stomach contents will be digested and incorporated in animal tissues. Analysis of carbon and nitrogen stable isotopes represent a longer period in the animal's lifecycle and have been recognized as an effective method to complement feeding ecology studies based on stomach contents of marine mammals (Knoff et al 2008, Gross et al 2009, Barros et al 2010, Kiszka et al 2010, Newsome et al 2010, Caut et al 2011. The basic principle of this technique is that the isotopic composition of consumers is derived from the isotopic composition of their food (e.g., Kelly 2000, Cherel et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The basic principle of this technique is that the isotopic composition of consumers is derived from the isotopic composition of their food (e.g., Kelly 2000, Cherel et al 2010. In marine systems, several studies have shown that there are consistent differences between the isotopic composition of animals living in pelagic vs. benthic environments, and among estuarine, nearshore and offshore environments (France 1995, Kurle & Gudmundson 2007, Cherel & Hobson 2007, Newsome et al 2010, Ohizumi & Nobuyuki 2010. Therefore, the use of stable isotopes can help identify the utilization of different habitats by species (Das et al 2003, Capelli et al 2008, Gross et al 2009, Newsome et al 2010, Pinela et al 2010.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations